Entrepreneurial Experience for Entrepreneurial Success in Ethnic Minang Entrepreneurs Indonesia - Emrizal, Emrizal; Primadona, Primadona; Suryani, Yosi; Neswardi, Sepri; Haries, Alfatah (Politeknik Negeri Bengkalis, 2024)
This study aims to find out how the influence of entrepreneurial experience on the success of ethnic Minangentrepreneurs. The people of West Sumatra live an entrepreneurial life and are famous for the Minang ethnicity andalmost 34 percent of them live migratory as entrepreneurs in all regions in Indonesia. This study uses a quantitativeapproach using 150 samples, namely Minang ethnic entrepreneurs who have been entrepreneurs for at least 5 years. Dataprocessing using SEM with PLS. The results of the study show that there is a significant influence betweenentrepreneurial experience and the success of ethnic Minang entrepreneurs.